The direct option - Bartlett, Dick, 1935- (Texas A & M University Press, 1994)
Party plans, individual calls, customer lists - this hands-on guide to a career in direct selling introduces readers to one of the fastest-growing sectors of the American economy. Companies such as Avon, Mary Kay, Shaklee, Amway, and Discovery Toys offer careers - part- or full-time - to millions of Americans, nine out of ten of whom are women. The beauty of direct selling is the ease of entry: low cost, no educational requirements, no age, ethnic, disability, or other barrier to achieving success.
Keywords: Direct selling -- United States -- Case studies.; Vente directe -- États-Unis -- Études de cas.; BUSINESS & ECONOMICS -- International -- Marketing.; BUSINESS & ECONOMICS -- Marketing -- Multilevel.; BUSINESS & ECONOMICS -- Exports & Imports.; Direct selling; United States; Commerce.; Business & Economics.; Marketing & Sales.; Case studies